Retention of carotenoids in orange-fleshed sweet potato during processing - Vimala, B. (Springer-Verlag, 2011)
The retention of carotenoids was studied in the storage roots of ten sweet potato clones possessing different intensities of dark orange-flesh colour in four different processing methods—oven drying, boiling, sun drying and frying. The results indicated that the extent of retention varied with the method of processing. The highest retention was observed in oven drying (total carotenoids 90%–91% and β-carotene 89%–96%) followed by boiling (total carotenoids 85%–90% and β-carotene 84%–90%) and frying (total carotenoids 77%–85% and β-carotene 72%–86%). The lowest retention of total carotenoids (63%–73%) and β-carotene (63%–73%) was recorded in the sun drying method.